Evaluación de seguridad y contaminación ambiental dentro de la actividad de transporte de carga pesada y excepcional en la organización Oretrans – Lima - Villa Trujillano, Carlos Gabriel (2012)
Using the present thesisdraft, we were able to determine that the level of security and environmental pollution in the heavytransport load and exceptional expires with the minimum standards, it was able to demonstrate through inspections carried out at the different transport units which were objects of study, this with the intention to identify and quantify the aspects that delayed deliveries of the different heavy goods and exceptional ofthe best customers ofthe Organization specializing in Transport S.A. C. was also conducted surveys, training sessions and trainings, to mitigate the negative environmental impacts that this generated during the development of the transport activity. Once identified the flaws, it was determined the corrective action based on the observations found, these corrective measures were based on the immediate deployment of equipment missing and damaged that were observed during the inspection. Also as a supplement is executed training and constant practice, emphasizing that were based on the observations found; so that in this way are formed by the positive habits of drivers, mechanics, assistants and skilled manoeuvrers, of having all your equipment needed for the implementation of the travel and can in this way to deliver the load time. On the other hand it was possible to detect that the great environmental problem that arises from this activity, we speak about the environmental pollution, by means of the generation of so lid residues; that are generated and thrown to the beds of the rivers and along the distance of the roads. Thanks to this fact it was possible to establish an initiative to estímate the Production Per capita of the residues, obtaining a PPC of 0.066 Kg 1 Kglpersona/day Kglpersona/day. This was achieved, by means of the compilation of the so lid residues for his temporary storage inside the base of the organization for his later sale from these to a trading Company of solid residues, those who huy the domestic waste and industrial type for subsequent treatment and final disposal and that it may be possible to comply with environmentallegislation. Key words: heavy transport load, environmental problem.